Improving Students’ Creative Writing Skill through Project Based Learning Using Wattpad as Learning Media Technology - Zubaidi, Zubaidi; Suharto, Ririn Pratiwi; Maulidiyah, Fitrotul (BRILIANT: Jurnal Riset dan Konseptual, 2023)
This study was conducted in English Grammar for Content and Creative Writing class. Project-based learning using Wattpad is implemented as a teaching model to improve students’ writing skills. They will accomplish two creative writing projects. This study aims to identify the implementation of project-based learning using Wattpad and students’ perceptions towards it. This research implemented a case study. The data were obtained from observation and questionnaires. Most students give positive attitudes toward the use of Wattpad and they liked to use Wattpad as a writing platform.